M(t)/M/1 Queueing System with Sinusoidal Arrival Rate - Pant, A. P.; Ghimire, R. P. (Journal of the Institute of Engineering, 2016)
This paper deals with the study of M (t)/M/1 queueing system with customers arrive to the system with sinusoidal arrival rate function λ (t) and are served exponentially with the rate μ. On formulating the mathematical model, we obtain the expressions for mean waiting time in the queue, mean time spent in the system, mean number of customers in the queue and in the system by using recursive method. Some numerical illustrations are also obtained by using computing software so as to show the applicability of the model under study. Journal of the Institute of Engineering, 2015, 11(1): 120-127